(untitled) (Mugda Medical College Journal, 2024)
Chronic kidney disease (CKD) is a worldwide health problem because of the significant morbidity and mortality which is mostly due to chronic inflammation and proteinuria. Early detection of inflammation and its proper management can prevent further CKD progression and complications. This study aims to observe the association of neutrophil-lymphocyte ratio (NLR) with inflammatory markers in chronic kidney disease stage 3 and 4. In this study, a total of 100 adult patients of CKD stage-3 and 4 were included as study subjects and patient with acute illness, known case of malignancy, cardiovascular and cerebrovascular disease were excluded from the study. From each patient all the relevant history, clinical and laboratory findings were recorded in the data collection sheet. Study subjects were divided into two groups according to NLR value; those who have NLR 0- 3 were in group normal NLR and subjects with NLR >3 in group high NLR. Then markers of inflammation ESR, CRP and serum albumin were compared between these groups. Statistical analysis was done by Statistical Package for Social Science (SPSS) version 22.0. The mean ESR of male and female patients was higher in high NLR subjects than normal NLR subjects. The mean CRP was higher in high NLR subjects than normal NLR subjects. The mean serum albumin was lower in high NLR subjects than normal NLR subjects. The difference of mean ESR, CRP was statistically significant between high NLR and normal NLR subjects but difference of mean serum albumin was not statistically significant. The study findings suggest that high NLR is significantly associated with of inflammatory markers-ESR, CRP. Hence, it can be concluded that NLR could be used as an indicator of inflammation in CKD. Mugda Med Coll J. 2024; 7(1): 4-8